Careers Shaman, Bless This Lab. - Karlin, S.
The ability to work across cultures has become as important as engineering prowess, particularly as high-tech firms open more and more overseas facilities, engage in multinational projects, and outsource to companies in still other countries. Engineers are now faced with the challenge of becoming more aware of cultural differences. This paper discusses the difficulties that can arise when working in a foreign environment and provides some useful advise on how to overcome these difficulties
Keywords: Cultural differences; High-tech firms; Multinational projects; Outsourcing; Overseas facilities; Working overseas